2018
DOI: 10.2478/helm-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

First report of entomopathogenic nematode Steinernema feltiae (Rhabditida: Steinernematidae) from Croatia

Abstract: SummaryA survey of entomopathogenic nematodes was conducted in Croatia between 2016 and 2017. The steinernematids were recovered in two out of 100 soil samples from agricultural land characterized as loamy soils with acidic reaction. Molecular and morphological identification was used to distinguish the nematodes. The isolates were identified as two different strains conspecific with Steinernema feltiae. The variations in morphometrical characteristics of infective juveniles (IJs) and males were observed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(30 reference statements)
1
5
1
Order By: Relevance
“…This result was similar to that reported by Brodie [ 31 ] from Fiji Islands (7.3%), Valadas [ 32 ] from Portugal (6.7%), and Hatting [ 33 ] from South Africa (5%). However, this rate was higher than those reported by Caoili [ 34 ] from the Philippines (2.5%), Majić [ 35 ] from Croatia (2.0%), and Noujeim [ 36 ] from Lebanon (1%). Higher prevalence of EPNs in soil from that determined in the present study was observed by Kanga [ 37 ] from Southern Cameroon (10.4%), Khatri-Chhetri [ 38 ] in Nepal (10.5%), and Malan [ 39 ] in South Africa (17%).…”
Section: Discussioncontrasting
confidence: 63%
“…This result was similar to that reported by Brodie [ 31 ] from Fiji Islands (7.3%), Valadas [ 32 ] from Portugal (6.7%), and Hatting [ 33 ] from South Africa (5%). However, this rate was higher than those reported by Caoili [ 34 ] from the Philippines (2.5%), Majić [ 35 ] from Croatia (2.0%), and Noujeim [ 36 ] from Lebanon (1%). Higher prevalence of EPNs in soil from that determined in the present study was observed by Kanga [ 37 ] from Southern Cameroon (10.4%), Khatri-Chhetri [ 38 ] in Nepal (10.5%), and Malan [ 39 ] in South Africa (17%).…”
Section: Discussioncontrasting
confidence: 63%
“…A survey took place between 2015 and 2016 years, and soil samples were collected randomly with a hand shovel from different habitats such as forest, pasture, field crops, vegetable, and fruit orchards following rainy days in spring (March-June) and autumn (September-October) (Majić et al 2018). A total of 112 soil samples were collected.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, some characters such as the body length of IJs were relatively less than those described S. feltiae originally. Some other researchers had the same results (Campos-Herrera et al, 2006; Majić et al, 2018;Flores et al, 2021). It has been suggested that IJs body length is the longest when EPNs are raised at 8°C and this character could be limited at higher room temperature conditions (Hazir et al, 2001).…”
Section: Discussionmentioning
confidence: 56%